2018
DOI: 10.1149/2.0831809jes
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Water Evaporation Rates in Gas Diffusion Layers of Fuel Cells

Abstract: The efficiency of polymer electrolyte fuel cells is closely linked to effective heat and water management. Evaporation of water in the gas diffusion layers (GDL) is an important process influencing water management and can even be used for evaporative cooling. In this study, evaporation rates in Toray-GDL materials are obtained for different temperatures, gas flow rates, carrier gases and water saturation levels. Evaporation rates are correlated with water distribution profiles in the GDL, obtained using X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…Thus, for any gas velocity, a GDL thickness reduction only increases the total evaporative water removal if L is small enough to avoid fully saturating the gas channel. This effect of increased evaporation rates has been observed experimentally by Lal et al [21] who, with a comparable setup, observed that a thickness reduction from TGP-H 120 to TGP-H 060 resulted in an evaporation rate increase that was lower than expected from the reduction in diffusive path length.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Thus, for any gas velocity, a GDL thickness reduction only increases the total evaporative water removal if L is small enough to avoid fully saturating the gas channel. This effect of increased evaporation rates has been observed experimentally by Lal et al [21] who, with a comparable setup, observed that a thickness reduction from TGP-H 120 to TGP-H 060 resulted in an evaporation rate increase that was lower than expected from the reduction in diffusive path length.…”
Section: Resultssupporting
confidence: 79%
“…This GDL was chosen to keep overall evaporative fluxes moderate to avoid thermal gradients as much as possible. The onset of thermal limitations was observed for thinner GDLs at 80 • C in a similar setup [21]. A seal was placed around the GDL, preventing leakage of vapor and controlling the GDL compression.…”
Section: Materials and Setupmentioning
confidence: 75%
See 2 more Smart Citations
“…These formulas explicitly include the liquid-gas interfacial area density a lg , which is unknown a priori, making even an estimation of the rates difficult. [179,180] and Toray TGP-H-060 [181] were recast into the form of Eq. 18 and shown as heart symbols.…”
Section: Evaporation and Condensationmentioning
confidence: 99%